An investigation of process capability indices - Pang, May Choo (2008)
In industry today, process capability indices (PCI) are part of the day-to-day decision making in designing, process improvement, suppliers selection and many other important technical and business decisions. But, several statisticians and practitioners are beginning to say "Stop using CPk". This report provides an overview of the controversy sparked by process capability analysis, researches into the various process capability indices computation and normality testings, and discusses the applications of PCI on size and geometrical tolerance. Statistical software is used whenever applicable to analyze the data.